LANDASAN PSIKOLOGIS PENGEMBANGAN KURIKULUM PAI - Priyanto (CV. Amerta Media, 2017)
Curriculum, both at the stage of the curriculum as an idea, a plan, experience and curriculum as a result, the development must refer to or use the foundation strong and sturdy, so that the curriculum can function and act in accordance with the demands of education to generate as stated in the formulation of national education goals outlined in Act No. 20 of 2003. In principle, the psychological aspect is the basic foundation should be the foundation of any curriculum development PAI. The cornerstone of psychological, are assumptions derived from psychology is used as a starting point in developing the curriculum. There are two types of psychology that should be the reference that developmental psychology and the psychology of learning. Learn the process of developmental psychology and developmental characteristics of students as subjects of education, while learning psychology study the behavior of learners in a learning situation. There are three types of learning theories that have large influence in curriculum development, namely cognitive learning theory, behavioristic, and humanistic. Psychological grounding can be implemented in PAI learning in three domains, namely; material PAI PAI learning process, and evaluation of learning PAI. Key Words: Curriculum, Platform Psychology, PAI